Children, Time Allocation, and Consumption Insurance - Blundell, Richard; Pistaferri, Luigi; Saporta-Eksten, Itay (Journal of Political Economy, 2018)
We study choices of households deciding on consumption and allocation of spouses’ time to work, leisure, and child care. With uncertainty, the allocation of goods and time over the life cycle also serves the purpose of smoothing marginal utility in response to shocks. Combining data on consumption, wages, hours of work, and time spent with children, we compute the sensitivity of consumption and time allocation to transitory and permanent wage shocks. We find that family labor supply responses depend on three counteracting forces: complementarity of leisure time, substitutability of time in the production of child services, and added worker effects.